Displasia ectodérmia. Informe de tres casos. - Blanco Rabassa, Eladio; D. Álvarez, Gladys; del Toro, Pedro; de Armas, Antonio; Fragoso, Trini (Revista Cubana de Pediatría, 2023)
Presentar 3 casos de esta enfermedad.